1985
DOI: 10.1136/adc.60.12.1177
|View full text |Cite
|
Sign up to set email alerts
|

Brain revascularisation in hypertension.

Abstract: SUMMARY Neurological symptoms in hypertensive subjects may be a reflection of intracranial vascular disease and not just a consequence of hypertension. Two hypertensive children with renovascular disease, neurological symptoms, and severe cerebral arterial disease were treated by extracranial-intracranial arterial bypass surgery with improvement of symptoms and easier control of blood pressure. Where revascularisation surgery is appropriate, this should be undertaken before neurological complications arise.Ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
0
9
1
Order By: Relevance
“…Although the association between renovascular disease and widespread arterial involvement has been reported, 2,4,8,9,16 it seemed to be more extensive in our cohort than in other series, 7,14,[17][18][19][20][21][22][23] in which extensive investigations for widespread vascular stenoses were not performed. In our series, bilateral RAS was seen in 48% of patients and intrarenal disease in 45% of patients.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Although the association between renovascular disease and widespread arterial involvement has been reported, 2,4,8,9,16 it seemed to be more extensive in our cohort than in other series, 7,14,[17][18][19][20][21][22][23] in which extensive investigations for widespread vascular stenoses were not performed. In our series, bilateral RAS was seen in 48% of patients and intrarenal disease in 45% of patients.…”
Section: Discussioncontrasting
confidence: 60%
“…In addition, there was a high incidence of involvement of other vascular beds, particularly the brain (n ϭ 7; 21%) and aorta (n ϭ 8; 24%), in this study. Reportedly, the carotid and vertebral arteries are involved in 25% to 30% of patients with FMD, 5,9 and a non-Takayasu midaortic syndrome is well recognized in children. 24 Seven of our patients had severe cerebrovascular involvement.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…If renovascular intervention is considered electively, there may be a role for undertaking cerebral revascularization first. Interestingly, it has been observed that blood pressure tends to drop in children without renovascular disease who have undergone surgical revascularization, 18 presumably as the cerebral circulation is no longer so reliant on systemic blood pressure. The importance of maintaining circulating volume during periods of vomiting or diarrhoea and in the postoperative period cannot be overemphasized.…”
Section: Hypertensionmentioning
confidence: 99%